Population pharmacokinetic/pharmacodynamic study suggests continuous infusion of ceftaroline daily dose in ventilated critical care patients with early-onset pneumonia and augmented renal clearance. (5th September 2022) - Chauzy, Alexia; Gregoire, Nicolas; Ferrandière, Martine; Lasocki, Sigismond; Ashenoune, Karim; Seguin, Philippe; Boisson, Matthieu; Couet, William; Marchand, Sandrine; Mimoz, Olivier; Dahyot-Fizelier, Claire
Abstract: Objectives: Ceftaroline could be suitable to treat early-onset ventilator-associated pneumonia (VAP) because of its antibacterial spectrum. However, augmented renal clearance (ARC) is frequent in ICU patients and may affect ceftaroline pharmacokinetics and efficacy. The objective of the study was to explore the impact of ARC on ceftaroline pharmacokinetics and evaluate whether the currently recommended dosing regimen (600 mg every 12 h) is appropriate to treat VAP in ICU patients. Methods: A population pharmacokinetic model was developed using pharmacokinetic data from 18 patients with measured creatinine clearance (CLCR ) ranging between 83 and 309 mL/min. Monte Carlo simulations were conducted to determine the PTA and the cumulative fraction of response (CFR) against Streptococcus pneumoniae and MRSA for five dosing regimens. Study registered at ClinicalTrials.gov (NCT03025841). Results: Ceftaroline clearance increased non-linearly with CLCR, with lower concentrations and lower probability of reaching pharmacokinetic/pharmacodynamic targets when CLCR increases. For the currently recommended dosing regimen, the probability of having unbound ceftaroline concentrations above the MIC over the entire dose range is greater than 90% for MICs below 0.125 mg/L. Considering the distribution of MICs, this regimen would not be effective against MRSA infections (CFR between 21% and 67% depending on CLCR ), but would be effective against S. pneumoniae infections (CFR >86%). Conclusions: The recommended dosing regimen of ceftaroline seems sufficient for covering S. pneumoniae in ICU patients with ARC, but not for MRSA. Among the dosing regimens tested it appears that a constant infusion (50 mg/h) after a loading dose of 600 mg could be more appropriate for MRSA infections.